2021
DOI: 10.1177/0003134820988808
|View full text |Cite
|
Sign up to set email alerts
|

The Shortage of Trauma Surgeons in the US

Abstract: Background As the United States (US) population increases, the demand for more trauma surgeons (TSs) will increase. There are no recent studies comparing the TS density temporally and geographically. We aim to evaluate the density and distribution of TSs by state and region and its impact on trauma patient mortality. Methods A retrospective cohort analysis of the American Medical Association Physician Masterfile (PM), 2016 US Census Bureau, and Centers for Disease Control and Prevention (CDC’s) Web-based Injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…6,7,43 Our findings that United States' states/territories which experience a larger quantity of geriatric trauma patients generally experience fewer preventable mortalities may be to a greater quantity of trauma centers, and therefore access to care, for patients in highly populated areas. 43 Additionally, these findings could partially be due to these trauma centers having more frequent encounters with geriatric patients and local institutional policies which serve to increase the quality of care for older individuals has the ability to improve geriatric trauma patient outcomes. 44 This notion is further supported when considering that geriatric patients in Arizona were observed to have one of the lowest rates of preventable mortality and could be partly explained by the implementation of their "G60 Program," a set of trauma policies designed to increase survival and decrease longterm disability of geriatric individuals.…”
Section: Geographic Variation In Patient Safety Indicatorsmentioning
confidence: 71%
“…6,7,43 Our findings that United States' states/territories which experience a larger quantity of geriatric trauma patients generally experience fewer preventable mortalities may be to a greater quantity of trauma centers, and therefore access to care, for patients in highly populated areas. 43 Additionally, these findings could partially be due to these trauma centers having more frequent encounters with geriatric patients and local institutional policies which serve to increase the quality of care for older individuals has the ability to improve geriatric trauma patient outcomes. 44 This notion is further supported when considering that geriatric patients in Arizona were observed to have one of the lowest rates of preventable mortality and could be partly explained by the implementation of their "G60 Program," a set of trauma policies designed to increase survival and decrease longterm disability of geriatric individuals.…”
Section: Geographic Variation In Patient Safety Indicatorsmentioning
confidence: 71%
“…Today, trauma surgeon density in the United States has plateaued. 16 While there are little data in surgery, EM and critical care medicine can both provide insight into what is reasonable work for physicians caring for sick patients. A survey of physicians responsible for creating ICU schedules found that an average FTE worked 24 weeks per year, including 24 weekend days and zero overnight calls.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, what is "ideal" for a division may not reflect "ideal" workload for individual surgeons. In the era of ACS shortages and high levels of burnout, this definition is needed more than ever 15,16 Acute care surgery in the United States is at a breaking point with increasing volumes and a shortage of surgeons covering trauma and emergency surgical services. 17 This has not improved over the last 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…Second, as the AAMC State Physician Workforce Profile database used in this analysis was constructed utilizing data from the AMA Physician Masterfile, the self-reporting practices associated with this database may underestimate or overestimate the number of practicing physicians, however as this database has successfully been utilized in surgical research, this inaccuracy is likely minimal. 6 Lastly, due to a lack of demographic data in the AAMC State Physician Workforce Profile, we were unable to sub-stratify our analysis by race/ ethnicity and gender to comment on socio-demographic differences in the fields analyzed. 40 We offer several recommendations moving forward.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Physician shortages impact access to care and negatively impact patient outcomes, as a 2021 study demonstrated increased mortality rates in regions with a lower concentration of trauma surgeons per population. 6 The physician shortage is estimated to have differing effects in the national, regional and state settings, supply and demand models predicting that the Southern and Western US regions will be the most heavily affected by the year 2030, which has been further supported by data from the Health Resources and Services Administration (HRSA) which detail Florida and Texas experiencing the greatest shortages. 7,8 The root of this projected physician shortage can be traced to government funding provided for Graduate Medical Education (GME) residency programs and the numerous changes this funding source has experienced.…”
Section: Introductionmentioning
confidence: 99%